Sport activity in the context of subjective well-being of university students - Pašková, Lucia; Sližik, Miroslav; Blahutková, Marie; Górny, Mirosław Paweł; Benedik, Ľudovít (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. In our research we were particularly interested in answering the question whether there is a relationship between a person’s comfort or well-being in relation with the sporting activity of adolescents. Aim of Study. The aim of the research was to analyse the relationship between physical activity and subjective well-being of university students. Material and Methods. The research was carried out on a group of university students studying at different types of universities. The research group consisted of 150 men and 230 women with an average age of 20.81 years. For data collection we used: questionnaire of emotional habitual subjective well-being and questionnaire of life satisfaction. The data obtained in this way were subjected to statistical analysis of x2 test and Spearman correlation coefficient. Results. We have found that active sports respondents at a nonprofessional level compared to passive athletes are more likely to experience a sense of physical freshness and enjoyment. On the other hand, the non-sportsmen are more likely to experience fear and pain. Our findings clearly confirm the correlation coefficients between active sports and the frequency of positive emotions. On the other hand, we found negative correlations in the relationship between active sports and the experience of negative emotions. In the case of a higher level of sports performance, we found significant negative weak to medium close relationships with the frequency of survival of negative emotions, and significant positive moderate relationships were shown by survival of physical freshness, enjoyment and joy. In the case of relationships between top sports and the emotional component of subjective well-being, we found weak to moderate relationships with the enjoyment, guilt and shame. Sports activity leads to increased life satisfaction, which confirmed number of correlations between active non-professional sports and overall life satisfaction. Conclusions. Our research findings have confirmed that physical activity even if in a minimum rate, increases the subjective well-being of adolescents as well as self-satisfaction and contributes to more frequent positive emotions or increased adolescents’ life satisfaction.
Keywords: subjective quality of life; impact of sport; life satisfaction; emotions; self-evaluation